2011
DOI: 10.1186/1471-2334-11-182
|View full text |Cite
|
Sign up to set email alerts
|

Severe morbidity and mortality in untreated HIV-infected children in a paediatric care programme in Abidjan, Côte d'Ivoire, 2004-2009

Abstract: BackgroundClinical evolution of HIV-infected children who have not yet initiated antiretroviral treatment (ART) is poorly understood in Africa. We describe severe morbidity and mortality of untreated HIV-infected children.MethodsAll HIV-infected children enrolled from 2004-2009 in a prospective HIV programme in two health facilities in Abidjan, Côte d'Ivoire, were eligible from their time of inclusion. Risks of severe morbidity (the first clinical event leading to death or hospitalisation) and mortality were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…While, there have been success stories coming out of Africa with respect to the PMTCT programs, the vast majority of the affected do not have access to these programs 7 . Studies have also demonstrated the benefits of early care and antiretroviral therapy in reducing morbidity and mortality in HIV infected children 13,14,15 . This informed the World Health Organization (WHO) policy statement that all HIV infected children less than 24 months be commenced on highly active anti-retroviral therapy (HAART) as soon as HIV diagnosis is made.…”
Section: Challenges Of Pediatric Hiv In Sub-saharan Africa and Other mentioning
confidence: 99%
“…While, there have been success stories coming out of Africa with respect to the PMTCT programs, the vast majority of the affected do not have access to these programs 7 . Studies have also demonstrated the benefits of early care and antiretroviral therapy in reducing morbidity and mortality in HIV infected children 13,14,15 . This informed the World Health Organization (WHO) policy statement that all HIV infected children less than 24 months be commenced on highly active anti-retroviral therapy (HAART) as soon as HIV diagnosis is made.…”
Section: Challenges Of Pediatric Hiv In Sub-saharan Africa and Other mentioning
confidence: 99%
“…When untreated, HIV-infected children experience increased risks of severe morbidity and mortality, through immunodeficiency [25]. Antiretroviral therapy (ART) is the standard treatment of HIV [6].…”
Section: Introductionmentioning
confidence: 99%
“…It others setting very high mortality rate where found in infants who were not on ARV compared to those receiving ARV treatment (14). Death occurred in our study at a median age of 7 months; HIV infection increased the death rate before the age of 2 years considerably (39,40).…”
Section: Discussionmentioning
confidence: 68%
“…Before that Blanche et al showed that 44% of HIV-1 infected infants born to mothers with severe disease at delivery, will die during the first 18 months of life as a result of HIV encephalopathy and opportunistic infections (12). Rapid progressors are infants who develop severe signs of AIDS very early in life usually leading to death for most of them (13,14). Many factors are described in literature concerning HIV-infected rapid progressors (15)(16)(17)(18).…”
Section: Original Articlementioning
confidence: 99%